2017
DOI: 10.1016/j.finel.2017.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonal micro-cutting modeling of the Ti17 titanium alloy using the crystal plasticity theory

Abstract: The development of computation means has allowed the simulation of complex mechanical problems. The first simulations of manufacturing processes at the microstructure scale, namely in the field of machining, have recently emerged. In this study, and on the basis of previous research, a novel approach to machining simulation is proposed. A crystal plasticity behavior law has thus been implemented and its parameters have been identified, for each of the two phases constituting the material. This is achieved thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 54 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…The machined surface in Figure 8g had more obvious plowing, bulging, and sticky chip, which adversely affected the quality of the machined surface. The sticky chips on the machined surface in Figure 8h appeared in a larger area due to the increased friction, extrusion between tool-chip and tool-workpiece, and increased heat generated by cutting [14], which intensified chip adhesion. The sticky chip on the machined surface reduced at 1800 mm/min (Figure 8i).…”
Section: Surface Morphology At Different Cutting Speedsmentioning
confidence: 99%
See 1 more Smart Citation
“…The machined surface in Figure 8g had more obvious plowing, bulging, and sticky chip, which adversely affected the quality of the machined surface. The sticky chips on the machined surface in Figure 8h appeared in a larger area due to the increased friction, extrusion between tool-chip and tool-workpiece, and increased heat generated by cutting [14], which intensified chip adhesion. The sticky chip on the machined surface reduced at 1800 mm/min (Figure 8i).…”
Section: Surface Morphology At Different Cutting Speedsmentioning
confidence: 99%
“…Zhao M et al [13] prefabricated four AA7075 aluminum alloys, investigated the influence of crystal orientation on the grinding force, and established a micro-grinding force prediction model. Ayed Y et al [14] performed a cutting simulation on Ti17 and investigated the effect of crystal orientation on chip formation and cutting force evolution. In addition, the cutting process was a complex thermal-force coupling process, accompanied by a high strain rate of plastic deformation and tool wear.…”
Section: Introductionmentioning
confidence: 99%
“…A crystal plasticity based model was applied to describe the individual behavior of the HCP α and the BCC β phases. Ayed et al [3] extended the above approach by suggesting a 3D modelling of the grains by Voronoi cells. According to the authors, a notable change in the β-grains orientations was observed during cutting process.…”
Section: Introductionmentioning
confidence: 99%
“…Many numerical models have been developed to study fracture for polycrystalline materials ( [4], [5], [6]). Recently, the phase field model has proven to be a powerful tool to simulate complex cracking phenomena ( [7], [8]).…”
Section: Introductionmentioning
confidence: 99%